CSRC oral communication and corporate disclosure - Hou, Chenxue; Wang, Qijian (Journal of Corporate Finance, 2023)
Oral communication has increasingly been used as a policy tool by the China Securities Regulatory Commission (CSRC) to regulate the Chinese financial market. However, less is known about whether and how this newly developed policy tool affects corporate decisions. Using machine-learning techniques, this paper develops a measure to evaluate the CSRC's oral emphasis on financial disclosure based on transcripts of its press conferences and official speeches. We find that when the CSRC places more emphasis on disclosure, both the quantity and quality of corporate disclosure are improved. Further evidence suggests that listed firms with external financing plans respond more to CSRC oral communication. Moreover, under political pressure, state-owned enterprises (SOEs) comply more with CSRC oral communication in terms of disclosure quantity but not disclosure quality.